António Lobo Antunes cronista: entre escritas de si e figurações de personagem - Becker, Caroline Valada (2013)
The chronicle is in a threshold, because it belongs to the literary scope and to the journalistic production it is published on periodicals and, later, compiled on a book. This assertion is a commonplace, but not very elucidating. This work aims at showing the specifities of this kind of text to understand it and reveal the structural signs of its realizations. To do that some of the António Lobo Antunes‟ chronicles were selected: the corpus for analysis is composed by four books from this author - Livro de crónicas (1998), Segundo livro de crónicas (2002), Terceiros livro de crónicas (2005) and Quarto livro de crónicas (2011). Through the lecture, it is possible to verify that Lobo Antunes‟ chronicles contain some of the typical tendencies of this textual genre. On the other hand, in a very expressive way, there is the chronicler‟s presence (empirical author), by the textual inscription memories are evocated and considerations are declared, creating a persona. There are, also, the circumstances in which occurs the character‟s figurations. That is how the António Lobo Antunes‟s chronicles as a textual genre are established, and this work aims at studying the way on how both tendencies appear in these texts.